Gingival hyperplasia: An initial oral manifestation of acute myeloid leukemia - Jitendra Sharan; Sonali Mohapatra; Gaurav Chhabra; Somanath Padhi; Sandhya Biswal; Uday Hemant Barhate; Ashok Kumar Jena (Wolters Kluwer Medknow Publications, 2023)
Various systemic diseases can manifest oral signs and symptoms early, which may be crucial for diagnosis and outlining the treatment plan. This case report highlights the presentation of acute leukemia (a malignancy of white blood cells) in a young female. An 11-year-old girl presented with gingival overgrowth and bleeding from the gingiva, weakness, and recent history of weight loss. A detailed workup consisting of complete blood count, bone marrow examination, flow cytometric immunophenotyping, cytogenetics, and molecular studies were carried out. The investigations confirmed the infiltration of blast cells of myelomonocytic origin, and a confirmatory diagnosis of acute myeloid leukemia (French-American-British classification M5) was made. The patient was put on induction chemotherapy and responded well. She developed febrile neutropenia following chemotherapy, which was managed conservatively. Gingival overgrowth subsided after the chemotherapy, and at the time of discharge, she was asymptomatic and hemodynamically stable. The oral health-care professionals must recognize that gingival overgrowth/enlargement may represent an initial manifestation of an underlying systematic disease.